2016
DOI: 10.1242/jeb.144311
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of instinctive and learned reward-related behaviors in honey bees

Abstract: We used transcriptomics to compare instinctive and learned, rewardbased honey bee behaviors with similar spatio-temporal components: mating flights by males (drones) and time-trained foraging flights by females (workers), respectively. Genome-wide gene expression profiling via RNA sequencing was performed on the mushroom bodies, a region of the brain known for multi-modal sensory integration and responsive to various types of reward. Differentially expressed genes (DEGs) associated with the onset of mating (62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…25 To validate the method and results, we ran two sets of control analyses. Honey bee control gene sets were derived from two RNA-seq expression sets from honey bee MB: (i) DEGs comparing active and inactive male honey bees (44) and (ii) DEGs comparing worker bees trained to forage at specific times of day (45). Human control gene sets were derived as follows.…”
Section: Methodsmentioning
confidence: 99%
“…25 To validate the method and results, we ran two sets of control analyses. Honey bee control gene sets were derived from two RNA-seq expression sets from honey bee MB: (i) DEGs comparing active and inactive male honey bees (44) and (ii) DEGs comparing worker bees trained to forage at specific times of day (45). Human control gene sets were derived as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Egr-1 and Hr38 expression levels were already slightly but significantly increased at t 0 compared to BF. This expression difference might be a result of flight activity in search for the known feeder or even anticipation of foraging activity (Naeger & Robinson, 2016). The foraging-induced IEG response is accompanied by an upregulation of downstream genes.…”
Section: Discussionmentioning
confidence: 99%
“…First, Egr-1 has been suggested to be one of the major transcription factors regulating gene expression changes during the transition from nursing to foraging (Khamis et al, 2015). Second, Egr-1 expression is upregulated during orientation flights and in anticipation of mating flights (Lutz & Robinson, 2013;Naeger & Robinson, 2016). Lutz & Robinson (2013) also demonstrated that Egr-1 upregulation is a consequence of higher sensory processing and learning instead of motor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the bees were from three independent colonies in each experiment (one colony was used in both experiments) and they were collected 2 years apart. These factors have been shown to have a strong influence on brain gene expression in honey bees . Hence, the similarity between these two experiments increases our confidence in the experimental design and in the robustness of the similarities.…”
Section: Discussionmentioning
confidence: 99%